Pilot study of transcranial photobiomodulation of lymphatic clearance of beta-amyloid from the mouse brain: breakthrough strategies for non-pharmacologic therapy of Alzheimer’s disease - Zinchenko, Ekaterina (Biomed Opt Express, 2019)
In this pilot study, we analyzed effects of transcranial photobiomodulation (tPBM, 1267 nm, 32 J/cm(2)) on clearance of beta-amyloid (Aβ) from the mouse brain. The immunohistochemical and confocal data clearly demonstrate the significant reduction of deposition of Aβ plaques in mice after tPBM vs. untreated animals. The behavior tests showed that tPBM improved the cognitive, memory and neurological status of mice with Alzheimer’s disease (AD). Using of our original method based on optical coherence tomography (OCT) analysis of clearance of gold nanorods (GNRs) from the brain, we proposed possible mechanism underlying tPBM-stimulating effects on clearance of Aβ via the lymphatic system of the brain and the neck. These results open breakthrough strategies for a non-pharmacological therapy of Alzheimer’s disease and clearly demonstrate that tPBM might be a promising therapeutic target for preventing or delaying Alzheimer’s disease.